THE CURRENT STATUS OF RESEARCH ON HARMFUL ALGAL BLOOM (HAB) IN INDONESIA - Boy Rahardjo Sidharta (JOURNAL OF COASTAL DEVELOPMENT, 2005)
Harmful Algal Bloom (HAB) is a natural phenomenon, however its incident increases both in term of cases and areas. When HAB outbreaks occur it will usually damage the environment and create economic losses. Environmental damage and economic losses are caused by the harmful aspects of the HAB organisms due to both of environmental alterations and toxin productions. In Indonesian seas, HAB has become more frequent and spread through out the country since 1970s. But there are still lacks of: number of researcher and research, funding support, awareness, and integrated national agenda with regard to HAB in Indonesia. In contrast, worldwide research and researchers, funding, awareness, and national agenda have become common and more advance. Hence, there are some opportunities for Indonesian researchers on HAB to: join (international) research projects, gain research funding, experience advance training, and pursue scholarships (for Masters and PhDs degree) from institutions abroad.